VD_FINDINFO Arrêt / 2014 / 861 vom 9. März 2015 - VD Tribunal cantonal (2015)
PRESCRIPTION, PÉREMPTION DU DROIT DE FIXER LES COTISATIONS, PÉREMPTION DE L'EXÉCUTION DE LA DÉCISION, PÉREMPTION | 10 LAVS, 16 LAVS, 30ter LAVS, 5 LAVS, 8 LAVS